Design optimization of a phase-change capacitive sensor for irreversible temperature threshold monitoring and its eco-friendly and wireless implementation - James Bourely; Danick Briand (Journal of Science: Advanced Materials and Devices)
Monitoring the temperature of perishable goods during transport and storage is essential to prevent waste and maintain product quality. Exploiting the unique property of phase-change materials (PCM), altering their physical state at specific temperatures, we optimize a capacitive sensor design based on a copper on polyimide interdigitated spiral (IDE) structure coated with a PCM to irreversibly detect temperature thresholds. The effect of the sensor dimensioning on its response is analyzed using a finite element model simulation. The model predicted up to 51% capacitance variation for optimal coverage of the PCM after spreading over the IDE, which was validated experimentally within a 5% error. Two melting concepts utilizing the spreading or the removal of the melted PCM over the IDE are investigated based on a capillary retention mechanism to maintain sensor sensitivity under inclination. Finally, an eco-friendly implementation of the capacitive structure and its wireless operation at 460 MHz is demonstrated on paper with a printed zinc transducer passivated with beeswax and covered with jojoba oil. Melting of the oil at a threshold temperature of 12.3 °C resulted in an irreversible shift in resonance frequency of 14 MHz. This study provides guidelines for the design and implementation of irreversible temperature monitoring capacitive sensors.